Privatization processes from the viewpoint of competition policy: the venezuelan experience 1993 - 1997 - Leidenz, Claudia Curiel (Revista do IBRAC, 2025)
The purpose of this study is to show the Venezuelan experience in relation to the introduction of competition policy in privatization processes. In Venezuela, the legal tool that regulates economic freedom is the Law to Promote and Protect the Exercise of Free Competition and within that legal text there are no express guidelines in relation to privatization processes.